On few-class Q-polynomial association schemes: feasible parameters and nonexistence results - Gavrilyuk, Alexander (Ars mathematica contemporanea, 2021)
We present the tables of feasible parameters of primitive 3-class ?$Q$?-polynomial association schemes and 4- and 5-class ?$Q$?-bipartite association schemes (on up to 2800, 10000, and 50000 vertices, respectively), accompanied by a number of nonexistence results for such schemes obtained by analysing triple intersection numbers of putative open cases.
Keywords: asociativna shema; association scheme; distance-regular graph; dopustni parametri; feasible parameters; Q-polinomska lastnost; Q-polynomial; razdaljno regularen graf